Surgical Causes of Recurrent Carpal Tunnel Syndrome - Khalid Ali; Esam Alnajar (Scientific Journal of University of Benghazi, 2018)
The aim of this research is to characterize the most common causes of recurrent carpal tunnel syndrome. Cases that were included in this study subjected to a detailed history and examination. The diagnosis was confirmed by electrophysiological studies and intraoperative findings. This study demonstrates that, all patients were found to have fibrosis surrounding the median nerve, which was attached to the radial leaf of the transverse carpal ligament, except one patient whose median nerve was found to have an adhesion to the subcutaneous tissue and 6% of the cases were found to have the incomplete release of the flexor retinaculum.